Przemiany społeczno-demograficzne w wielkich osiedlach mieszkaniowych Łodzi w okresie transformacji - Szafrańska, Ewa (Space – Society – Economy, 2013)
Large housing estates built after Second World War are often seen as a problematic areas in many cities all over Europe. This paper focuses on large housing estates in Łódź. The purpose of this study is to characterise the socio-demographic structure in nine largest housing estates in Łódź in the light of statistical data such as: age structure of population, household types, educational structure and identify changes which have occurred during the transformation period in these estates. In this paper it is shown that the socio-demographic changes observed in the estates, e.g. ageing population, increase in the number of single-person households, decreased percentage of active earners, and improved education background coincide with the processes that are taking place in the entire city and vary by period of their construction.